First-line toripalimab plus chemotherapy versus chemotherapy for advanced esophageal squamous cell carcinoma: A cost-effectiveness analysis - Jing-Wen Han; Yu Zhong; Jin Zhong; Wen-Jing Zeng; Li-Jun Sun (PLoS ONE, 2025)
Objectives This study aims to evaluate the cost-effectiveness of toripalimab combined with chemotherapy versus chemotherapy alone as a first-line treatment for advanced esophageal squamous cell carcinoma (ESCC) from the perspective of U.S. healthcare payers. Methods A 10-year partitioned survival model was developed using survival data from the JUPITER-06 clinical trial (NCT03829969). Costs included only direct medical expenses, and health utility values were derived from published literature. One-way and probabilistic sensitivity analysis were performed to assess the robustness of the model. Results Toripalimab combined with chemotherapy incurred an incremental cost of $64,483.3 and achieved an incremental effectiveness of 0.53 quality-adjusted life-years (QALY) compared to chemotherapy alone, resulting in an incremental cost-effectiveness ratio (ICER) of $122,771.67 per QALY. This ICER is below the willingness-to-pay threshold in the United States ($150,000). The model results were sensitive to the cost of toripalimab and the utility values of both progression-free and progressed disease states. Conclusions The findings indicate that toripalimab combined with chemotherapy as a first-line treatment for advanced ESCC in the United States provides a cost-effective benefit in comparison to chemotherapy alone.